2005
DOI: 10.1074/jbc.m500265200
|View full text |Cite
|
Sign up to set email alerts
|

RECQ1 Helicase Interacts with Human Mismatch Repair Factors That Regulate Genetic Recombination*[boxs]

Abstract: Understanding the molecular and cellular functions of RecQ helicases has attracted considerable interest since several human diseases characterized by premature aging and/or cancer have been genetically linked to mutations in genes of the RecQ family. Although a human disease has not yet been genetically linked to a mutation in RECQ1, the prominent roles of RecQ helicases in the maintenance of genome stability suggest that RECQ1 helicase is likely to be important in vivo. To acquire a better understanding of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
97
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 55 publications
2
97
0
Order By: Relevance
“…In addition, HsBLM interacts with HsMLH1 and HsExoI and, in conjunction with TopIIIa and both RMI1and RM2, has been shown to dissolve double Holliday junctions (Langland et al 2001;Pedrazzi et al 2003;Wu and Hickson 2003;Nimonkar et al 2011). HsRECQ1 (Doherty et al 2005) and HsWRN (Saydam et al 2007) also interact with HsMLH1, and HsRECQ1 as well as with HsExoI (Cui et al 2004). Furthermore, purified HsRECQ1 forms a subnanomolar affinity complex with HsMSH2-HsMSH6, and HsMSH2-HsMSH6 stimulates HsRECQ1 helicase activity on the 3 0 -flap structures (Doherty et al 2005).…”
Section: Parallels Between Yeast and Mammalian Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, HsBLM interacts with HsMLH1 and HsExoI and, in conjunction with TopIIIa and both RMI1and RM2, has been shown to dissolve double Holliday junctions (Langland et al 2001;Pedrazzi et al 2003;Wu and Hickson 2003;Nimonkar et al 2011). HsRECQ1 (Doherty et al 2005) and HsWRN (Saydam et al 2007) also interact with HsMLH1, and HsRECQ1 as well as with HsExoI (Cui et al 2004). Furthermore, purified HsRECQ1 forms a subnanomolar affinity complex with HsMSH2-HsMSH6, and HsMSH2-HsMSH6 stimulates HsRECQ1 helicase activity on the 3 0 -flap structures (Doherty et al 2005).…”
Section: Parallels Between Yeast and Mammalian Systemsmentioning
confidence: 99%
“…4; Table 1). Among the five known human RecQ family helicases, three, HsRECQ1 (Doherty et al 2005), HsBLM (Pedrazzi et al 2003), and HsWRN (Saydam et al 2007), have been shown to interact with the HsMSH2-HsMSH6 heterodimer. HsBLM and HsWRN also interact with the HsMSH2-HsMSH3 heterodimer (Pedrazzi et al 2003;Saydam et al 2007).…”
Section: Parallels Between Yeast and Mammalian Systemsmentioning
confidence: 99%
“…MGMT repairs the O(6)-alkyl-guanine mismatches dependent on MutS␣/MutL␣/EXO1 [13,14]. MutS␣ stimulates RECQL helicase activity; RECQL stimulates EXO1 incision activity and interacts with MLH1 [16]. 62 replication, recombination, and repair [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…MutS␣ stimulates RECQL helicase activity; RECQL stimulates EXO1 incision activity and interacts with MLH1 [16]. 62 replication, recombination, and repair [16,17]. TP73, a member of the p53 family, is involved in cellular responses to stress and development [18].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, RAD51-mediated replication fork reversal induced by sublethal genotoxic treatment with agents that interfere with the normal progression of replication is antagonized by poly (ADP-ribose) polymerase (PARP)/ RECQL-regulated restart, 26 leading us to speculate that the direct interaction between RECQL and RAD51 27 may affect their cross-talk at stalled replication forks. RECQL was also found to physically and functionally interact with mismatch repair factors that are implicated in cancer suppression, 28 which is likely to be important for the mechanism(s) whereby RECQL regulates genetic recombination to suppress DNA damage and chromosomal instability. 27,29 …”
Section: Breast Cancer Susceptibility Genes Implicated In Dna Repairmentioning
confidence: 99%